EFEKTIVITAS PENAMBAHAN ZAT PENGATUR TUMBUH PADA STEK MIKRO TANAMAN PORANG (Amorphophallus muelleri Blume) DAN TALAS BENENG (Xanthosoma undipes K.Koch): Kata kunci: Stek mikro, auksin, thidiazuron, tunas, akar - Nur Fitriyah; Mawi Wahyudi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2022)
The objective of this study is to find out the effectiveness of the addition of Growing Regulatory Substances (ZPT) to shoots growth and roots at micro cuttings of Amorphophallus muelleri blume) and Xanthosoma undipes k.koch. Complete Random Design (RAL) was used in this study with 8 treatments: Z1 = Amorphophallus without ZPT(control), Z2 = Amorphophallus + Auxin 1.5 ml / L, Z3 = Amorphophallus + Thidiazuron 1 ppm, Z4 = Amorphophallus + Auksin 1.5 ml / L + Thidiazuron 1 ppm, Z5 = Xanthosoma without ZPT, Z6 = Xanthosoma + Auksin 1.5 ml / L, Z7 Xanthosoma +Thidiazuron 1 ppm, Z8= Xanthosoma +Auxin 1.5 ml/L + Thidiazuron 1 ppm, each treatment is repeated 5 times. The data was analyzed using ANOVA, if there were significant differences between treatments followed by BNT Test 5 %. The addition of auxin, thidiazuron and combination both have a noticeable effect on the percentage of cuttings growing, the height of seedlings, the number of leaves, the length and number of roots. The ability to grow in vegetative propagation is also influenced by the type and size of planting material and the presence of growing points on cuttings. Micro Cuttings of Xanthosoma undipes K.Koch have a higher regeneration ability comparing with Amorphophallus muelleri Blume.